2017
DOI: 10.1097/pcc.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

RBC Distribution Width: Biomarker for Red Cell Dysfunction and Critical Illness Outcome?*

Abstract: Objective Red blood cell distribution width (RDW) is reported to be an independent predictor of outcome in adults with a variety of conditions. We sought to determine if RDW is associated with morbidity or mortality in critically ill children. Design Retrospective observational study. Setting Tertiary pediatric intensive care unit. Patients All admissions to Saint Louis Children’s Hospital Pediatric Intensive Care Unit between 1/1/2005 and 12/31/2012. Interventions We collected demographics, laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 36 publications
2
17
0
9
Order By: Relevance
“…13,21 Said et al also found a significant relation between admission RDW as well as relative RDW (calculated as the difference between the first day RDW and highest of the first seven days RDW divided by admission RDW) with mortality. 19 Similar to our study, Khanbabaee et al found a positive correlation between admission RDW and mortality but they could not find any association between ΔRDW and mortality. 13 Some studies suggest that the clearance of RBC from the circulation is well-balanced in healthy individuals but reduced in diseased states; as a result there is an increase in the number of smaller RBCs in the circulation which increases the RDW in diseased conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…13,21 Said et al also found a significant relation between admission RDW as well as relative RDW (calculated as the difference between the first day RDW and highest of the first seven days RDW divided by admission RDW) with mortality. 19 Similar to our study, Khanbabaee et al found a positive correlation between admission RDW and mortality but they could not find any association between ΔRDW and mortality. 13 Some studies suggest that the clearance of RBC from the circulation is well-balanced in healthy individuals but reduced in diseased states; as a result there is an increase in the number of smaller RBCs in the circulation which increases the RDW in diseased conditions.…”
Section: Discussionsupporting
confidence: 89%
“…6,18 Similarly several studies have been conducted on children in paediatric intensive care units which have also found an association of high RDW with mortality. 5,[13][14][15]19,20 However some other studies have found that there is no relation between high RDW and mortality in children. 13,21 Said et al also found a significant relation between admission RDW as well as relative RDW (calculated as the difference between the first day RDW and highest of the first seven days RDW divided by admission RDW) with mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Even though we could not find a significant correlation of RDW and deformability, as described by Patel et al (2013), there was a significant difference between groups in RDW, a parameter defining the degree of anisocytosis. Approximately 24% of Fontan patients in this study reached pathologic values (≥14.5%), which might be caused by disturbed erythropoiesis, shortened life span or early reticulocyte release (Said et al, 2017). This result is in agreement with previous findings (Tomkiewicz-Pajak et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…Said et al, reported that both admission RBC distribution width and relative change in RBC distribution width correlated with mortality, fewer ICU-free days and ventilator-free days. 22 In ROC analyses of the relationship between RDW and mortality, the AUC for Admission RDW was 0.611 (95% CI, 0.076-0.218), whereas the AUC for PIM-2 score was 0.901 (95% CI, 0.908-1.166). Rambly et al, which did not exclude subjects who had received prior transfusions, reported that in all critically ill pediatric patients, RDW was independently associated with PICU mortality.…”
Section: Discussionmentioning
confidence: 96%